Les mutilations des corps masculins et féminins dans les contes de transmission orale et leurs effets symboliques - Nicole Belmont (Ateliers d'Anthropologie)
This article considers the meaning of violent episodes—recounting body dismemberments and mutilations followed by repairs—found in three orally transmitted European stories. The happy outcome that leads the manhandled heroes and heroines to meet their destiny evokes the violence of some of the rites of passage of young people, at the end of which they attain the possibility of marriage. No longer acted out, but recounted, they use what could be called a “body language”, a language that stages the body.